2017
DOI: 10.3126/jnhrc.v15i2.18205
|View full text |Cite
|
Sign up to set email alerts
|

Preference of Food-items and Physical Activity of Peri-urban Children in Bhaktapur

Abstract: Background: Though cardiovascular diseases are mostly seen in adulthood, foundation of diet and physical activity is largely formed during childhood. The study aimed to explore children's preference for diet and physical activity in a peri-urban area of Nepal because this is an important dimension to explore in the life-course approach to combat non-communicable diseases. Methods:We conducted a cross-sectional study to enquire young peri-urban children of Duwakot and Jhaukhel villages of Bhaktapur district, Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Constellation of urban and rural predisposing factors may increase the cardiovascular health vulnerability of the peri-urban communities. Findings from the similar settings in Kathmandu showed that nearly half of the study population had poor knowledge on cardiovascular health, and majority had “Red or unhealthy food” preference over “Green or healthy foods and were indulged in sedentary activities” 11, 12. Studies elsewhere13, 14, 15, 16, 17, 18 have also demonstrated a high prevalence of CVD risk factors both in urbanizing and rural communities.…”
Section: Introductionmentioning
confidence: 94%
“…Constellation of urban and rural predisposing factors may increase the cardiovascular health vulnerability of the peri-urban communities. Findings from the similar settings in Kathmandu showed that nearly half of the study population had poor knowledge on cardiovascular health, and majority had “Red or unhealthy food” preference over “Green or healthy foods and were indulged in sedentary activities” 11, 12. Studies elsewhere13, 14, 15, 16, 17, 18 have also demonstrated a high prevalence of CVD risk factors both in urbanizing and rural communities.…”
Section: Introductionmentioning
confidence: 94%
“…The Pediatric-adapted Liking Survey (PALS) is fast, has a high response rate in the PED, with good-to-excellent clinical-to-home test–retest reliability [22]. Furthermore, results from an assessment of children’s preference for food and physical activity (PA) can guide program planning [23]. Health promotion across the socio-ecological framework needs to develop healthy food and PA preferences in children [24].…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, os alimentos de sabor doce (laranja) são preferidos com maior frequência pelos pré-escolares. Estudo realizado com crianças asiáticas com idade entre 5 a 7 anos observou que as crianças apresentam preferências por alimentos vermelhos, abrangendo a categoria de alimentos não saudáveis (sorvetes, doces) em comparação a alimentos verdes, categorizados como saudáveis (frutas, verduras e legumes) (VAIDYA et al, 2017).…”
Section: Resultsunclassified